The Role of Al Mujahidin Muhammadiyah Islamic Boarding School in Developing the Entrepreneurial Spirit of Students - Mohammad Nurul Yaqin; Sedya Santosa; Abdur Razak (International Journal of Religion, Humanity and Cultural Heritage, 2025)
This research aims to analyze the role of the Muhammadiyah Al Mujahidin Islamic boarding school in developing an entrepreneurial spirit among students. Using a qualitative approach with a case study method, this research collected data through in-depth interviews, field observations, and document review. The research results show that the Muhammadiyah Al Mujahidin Islamic boarding school plays an important role in instilling and developing an entrepreneurial spirit among students through various programs and activities, such as entrepreneurial learning, practical training, business mentoring, and providing access to resources. Key factors that support this effort include strong commitment from Islamic boarding school leaders, life skills-based curriculum, partnerships with business actors, and empowerment of local potential. The findings of this research provide valuable insight into the strategic role of Islamic boarding schools in preparing students to become strong young entrepreneurs and contribute to community economic development.